2023
DOI: 10.1101/2023.02.15.23285965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An economic evaluation ofWolbachiadeployments for dengue control in Vietnam

Abstract: Background Dengue is a major public health challenge and a growing problem due to climate change. The release of Aedes aegypti mosquitoes infected with the intracellular bacterium Wolbachia is a novel form of vector control against dengue. However, there remains a need to evaluate the benefits of such an intervention at a large scale. In this paper, we evaluate the potential economic impact and cost-effectiveness of scaled Wolbachia deployments as a form of dengue control in Vietnam - targeted at the highest b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Even under scenarios that resulted in a net positive incremental cost of the intervention in some cities and time frames, the intervention was still found to be cost-effective. These results are consistent with previous international studies in Indonesia 45 and Vietnam, 46 where the Wolbachia method was also found to be cost-effective. Considering the cost-effectiveness criteria adopted by the Brazilian National Commission for the Incorporation of Technology in the SUS (CONITEC) for neglected diseases (BRL 120 thousand per DALY), the results of the Wolbachia method would fall far below this threshold.…”
Section: Discussionsupporting
confidence: 92%
“…Even under scenarios that resulted in a net positive incremental cost of the intervention in some cities and time frames, the intervention was still found to be cost-effective. These results are consistent with previous international studies in Indonesia 45 and Vietnam, 46 where the Wolbachia method was also found to be cost-effective. Considering the cost-effectiveness criteria adopted by the Brazilian National Commission for the Incorporation of Technology in the SUS (CONITEC) for neglected diseases (BRL 120 thousand per DALY), the results of the Wolbachia method would fall far below this threshold.…”
Section: Discussionsupporting
confidence: 92%
“…Post hoc quantification of the cost-effectiveness of dengue control through releases of Wolbachia-infected mosquitoes in Yogyakarta found that releases were cost-effective, costing approximately US$1500 per DALY averted. 40 Additional modeling studies examining the potential cost-effectiveness of theoretical releases in Singapore and Thailand found that programs would be cost-effective, costing US$50 000-100 000 42 and US$343-420 65,66 per DALY averted, respectively. While these results are not directly comparable with the results presented here, and come from a dengue-endemic region, it highlights the low costs associated with Wolbachia releases compared to the cost of dengue infection.…”
Section: Discussionmentioning
confidence: 99%
“…6 In recent years, the Wolbachia programme has been extensively studied in both large cities and tropical, resource-constrained regions, and has been found both efficacious in limiting the spread of Aedes-transmitted arboviruses and costeffective as a population-level strategy. [5][6][7]…”
Section: Dear Editormentioning
confidence: 99%